THE IMPORTANCE OF SONOGRAM IN THE DIAGNOSIS OF OVARIAN CANCER AND PEDAGOGICAL TECHNOLOGIES IN ITS TEACHING - Yusupova Feruza Nurmamatovna; Dekhkambayeva Zulfiya Abubakirovna (Modern American Journals, 2025)
This article analyzes the importance of sonography in the diagnosis of ovarian cancer and modern pedagogical approaches to teaching it in the medical education system. Ovarian cancer is one of the most dangerous oncological diseases among women and plays an important role in reducing the number of early detection and improving the quality of life. Sonography is a diagnostic tool that is safe, has high accuracy and is widely used. The article also outlines the benefits of using interactive and innovative pedagogical technologies in teaching Sonography. Simulation training, virtual environment training, training through AR/VR technologies have been noted to serve as an effective tool in shaping the knowledge and skills of medical students.
Keywords: Ovarian cancer, Sonography, ultrasound, diagnostics, medical education, pedagogical technologies.